Analysis of Key Audit Matters in CAC 40 and WIG 20 Audit Reports - Grzegorz WARZOCHA; Kamil BUJAK (Communications of International Proceedings, 2020)
This research is a continuation from the earlier work of its authors on the requirements to identify and report key audit matters (further also referred to as “Key Audit Matters” or “KAM”) in auditors’ reports and its objective is to update, summarize and present the results of the work performed in respect of the key audit matters determined and communicated in the independent auditors’ reports issued in conjunction with the audit of the 2017-2019 annual financial statements of CAC 40 and WIG 20 constituent companies. Research activities focused on reading of the reporting requirements in respect of key audit matters relating to audits of historical financial information as defined in the International Standards on Auditing (ISA) and examination of the auditors’ reports issued in conjunction with the audit of the 2017-2019 annual financial statements of the CAC 40and WIG 20 constituent companies listed on the Paris Stock Exchange (France) and Warsaw Stock Exchange (Poland). The main objective of the research was to confirm how the number and the nature of the Key Audit Matters for CAC 40 and WIG 20 constituent companies varied in the period covered by the research. For the purpose of the research it was tentatively assumed that both (1) the number and (2) the nature of Key Audit Matters identified and reported in conjunction with the audit of the annual financial statements of CAC 40 constituent companies for the financial years 2017-2019 would vary. It was further assumed that both (3) the number and (4) the nature of Key Audit Matters identified and reported in conjunction with the audit of the annual financial statements of WIG 20 constituent companies for the financial years 2017-2019 would also vary.
Keywords: Audit; Risk; Auditor’s Report; Key Audit Matters.